THE ROLE OF INFAQ AND SADAQAH TO IMPROVE COMMUNITY ECONOMIC DEVELOPMENT - Nurhapirah Tasnim; Riska Febrianti Aulia; Adelia Marwa Ujung; Tia Deza Pohan; Rizqa Amelia (Transpublika Publisher, 2023)
In the Indonesian context, the role of zakat, infaq, and shadaqah (collectively known as ZIS) has gained significance in seeking government assistance for the economy. These contributions have the potential to address poverty and improve the overall economic well-being of the people. To effectively utilize the benefits of ZIS, a well-structured management body is essential to oversee the collection and distribution of these charitable funds. This management body should be capable of efficiently and transparently managing the funds, ensuring that contributions are directed towards the right causes and effectively utilized to uplift the community's economy. This study aims to explore the impact of zakat, infaq, and shadaqah in seeking government assistance for the Indonesian economy. The study also highlights the importance of ZIS, which represents a form of love for Allah and can alleviate poverty. Therefore, a competent management body is necessary to oversee zakat, infaq, and alms, ensuring proper management and promoting economic improvement in the community. The methodology employed in this article involves a literature review, which includes collecting relevant articles guided by the researchers. Through the analysis of these articles, the researcher draws conclusions to be presented in this paper.